Perbedaan kualitas hasil radiograf periapikal antara film konvensional dan film instan di Instalasi Radiologi FKG Universitas Brawijaya Malang - Farihah Septina; Robbyn Reyvaldo (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: This study is aimed to look at the distribution of the quality of periapical radiographs produced by students using conventional films and instant films at the Faculty of Dentistry Universitas Brawijaya radiology installation. Material and Methods: The method used in this research is analytic descriptive with cross sectional sampling method. The research datas were primary data with a total of 20 periapical radiographs from each method. Data was analyzed by Spearman test in SPSS software. Results: Data were analysed using the Spearman rho correlation test which showed the results of ρ = 0,5. The results of periapical radiographs using conventional films as much as 65% were very good, 25% were good, and 10% were not acceptable. The results of periapical radiographs using instant film were 70% good, 15% very good, and 15% were not acceptable. Conclusion: There is no difference in the quality of the results of conventional periapical radiographs and instant films in the radiology installation of the Faculty of Dentistry Universitas Brawijaya Malang.